Effect of Alternaria alternata (Fr.) Keissl. on the physiology of Pea (Pisum sativum L.) - Noureen, Kashifa; Jabeen, Khajista; Iqbal, Sumera; Jahan, Summera; Javad, Sumera (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Alternaria alternata (Fr.) Keissl. is responsible for causing leaf spots and blight diseases on a large number of horticultural and agricultural crops including pea. The response and resistance of different pea varieties to this fungus might vary. Therefore, this study was aimed to investigate the varietal differences in the physiological response of Pisum sativum L. to A. alternata. Various physiological and biochemical parameters of two commercial pea varieties (Leina and Meature) were assessed at vegetative stage in pot experiment. Sterilized seeds were soaked in 1×105 mL conidial suspension of A. alternata for 15 min and control seeds were soaked in sterilized water. These sterilized seeds were sown in pots containing sterilized soil. In both varieties, germination percentage, germination rate, seedling vigor index, root and shoot length, dry and fresh biomass, leaf sugar, chlorophyll a, b, total chlorophyll and carotenoid contents, leaf osmotic potential, leaf relative water content, significantly decreased under A. alternata stress as compared to control. But proline and protein content significantly increased. It is concluded from the results that A. alternata caused adverse effects on the physiology of pea plant. The tested pea variety Leina was found to be more sensitive under fungal stress of A. alternata as compared to Meature and the extent of stress caused by both test varieties can be exploited in future studies.